Multifidus muscle size in adolescents with and without back pain using ultrasonography. Issue 1 (January 2018) - Rahmani, Nahid; Kiani, Ali; Mohseni-Bandpei, Mohammad Ali; Abdollahi, Iraj
Abstract: Objective: The purposes of this study were; a) to compare multifidus muscle cross sectional area (CSA) in male adolescents suffering from low back pain (LBP) with healthy male adolescents using ultrasonography (US), and b) to assess the correlation between multifidus muscle size and demographic variables. Methods: A random sample of 40 healthy boys (as a control group) and 40 boys with LBP (as an experimental group) at the age range of 15–18 years was recruited in the present cohort study. Multifidus muscle dimensions including CSA, antero-posterior and medio-lateral dimensions were measured at level of L5 in both groups using US. Results: The results of an independent t -test to compare multifidus muscle size between the experimental and control groups showed a significant difference between the two groups in terms of CSA, antro-posterior and medio-lateral dimensions so that the experimental group had smaller muscle size than the control group. A significant correlation was found between height, weight and body mass index (BMI) and multifidus muscle size, but no significant correlation was observed between age and muscle size. Pain intensity and functional disability index was significantly correlated with muscle size in the experimental group. Conclusions: According to the results, multifidus muscle size was decreased in 15–18 years old male adolescents suffering from LBP compared with their healthy counterparts. Further studies are needed to support the findings of the present study.